Indicadores de desempenho dos cursos de graduação em instituição de ensino superior brasileira: um estudo de caso sob a percepção dos gestores - Marcos Crepaldi; Carlos Alberto Diehl (Revista Iberoamericana de Educación, 2014)
This article aims to identify the utility of performance indicators in the assessment of undergraduate courses in the perception of courses higher coordinators in the Brazilian educational institution. Evaluate organizational management performance is tool used in gauging the degree of achievement of strategic objectives. Evaluate the performance of undergraduate courses is analyze the level of care to students ' needs, the labour market, of monitored, regulatory bodies and society in general. The diversity of approaches achieved by indicators performance in the performance evaluation gives greater credibility. The research has descriptive character. The data were collected in December 2011 together the managers of undergraduate program. The results show the perception of coordinators higher courses regarding the use of performance indicators related to teachers, school desistence, of result evaluating the Enade and teaching methodologies used.